2019
DOI: 10.5200/baltica.2018.31.16
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and geochemical composition of the Onega Ice Lake sediments

Abstract: An analysis of the mineral-geochemical composition and structure of the Holocene–Pleistocene bottom sediments was performed on Lake Polevskoye, a small lake in the northern Lake Onega area in Russian Karelia, which is considered representative to describe the Late Weichselian Onega Ice Lake sediments. The analysis was accomplished using modern analytical methods, including scanning electron microscopy and ICP-MS, which allowed us to interpret their genesis in a new light. It is assumed that the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This is due to the influence of long-range atmospheric transport (Krachler et al 2006;McConnell et al 2019), which traditionally enriches the landscapes of the Republic of Karelia and neighbouring regions (Vinogradova et al 2017;Slukovskii et al 2020c). Increased accumulation of Cd, Zn, and Mo was noted in both the recent and the background sediments, which may be associated with the peculiarities of the natural level of these metals in the territory of Karelia, because earlier their increased concentrations were noted in the sediments of small lakes in this region and in the sediments of Lake Onega (Strakhovenko et al 2018;Slukovskii 2020;Slukovskii and Dauvalter2020). At the same time, it should be borne in mind that Cd is also an agent for the long-range transport of pollutants, and that its increased accumulation in the recent layers of sediments of lakes in northern Europe largely depends on this process.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is due to the influence of long-range atmospheric transport (Krachler et al 2006;McConnell et al 2019), which traditionally enriches the landscapes of the Republic of Karelia and neighbouring regions (Vinogradova et al 2017;Slukovskii et al 2020c). Increased accumulation of Cd, Zn, and Mo was noted in both the recent and the background sediments, which may be associated with the peculiarities of the natural level of these metals in the territory of Karelia, because earlier their increased concentrations were noted in the sediments of small lakes in this region and in the sediments of Lake Onega (Strakhovenko et al 2018;Slukovskii 2020;Slukovskii and Dauvalter2020). At the same time, it should be borne in mind that Cd is also an agent for the long-range transport of pollutants, and that its increased accumulation in the recent layers of sediments of lakes in northern Europe largely depends on this process.…”
Section: Resultsmentioning
confidence: 97%
“…The analysis of the chemical composition of water and recent sediments of the largest waterbodies in Europe is a significant component in assessing their current ecological state (Davydova et al 1999;Flerov et al 2000;Wihlborg and Danielsson 2006;Virkutyte et al 2008;Strakhovenko et al 2018). This is of great importance for both the fundamental science and the practical application of the knowledge gained, given that most of the large lakes are actively used for economic and recreational purposes, and serve as sources of drinking water for settlements.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the composition and geochemical features of upper bottom sediments of the cores Lake Onego (upper 0-50 cm of sediment) showed that they belong to two different types [38,39]. Well water circulation in the lake, which provides deep-water composition near the bottom (20 cm above the bottom sediment), is generally scarcely different from the contents of the whole water body in O 2 , N organic , P and Si across all bottom sediment stations, and Mn and Fe in the first type of bottom sediment stations.…”
Section: Core Stratification Of the Bottom Sediment Of Lake Onego Mor...mentioning
confidence: 99%
“…During chemical composition analysis of FM nodules and crusts from these lakes, the constant presence of Ba and Fe in signifficant amounts in manganese zones was revealed, along with the presence of Mn and P impurities in the granular zones. The chemical composition of FM nodules from Lake Surgubskoe is as follows: granular zones (%): Fe (24-67), Mn (0-21), Ва (0-0.5), O (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), Р (0.5-2), and total (44-100); manganese zones (%): Fe (1-35), Mn (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), Ва (4-12), O , Р (0-1), and total (55-99).…”
Section: Geochemical Composition Of Bottom Sediments and Fmc Of Lakesmentioning
confidence: 99%
See 1 more Smart Citation